Dosis de pollinaza en las características vegetativas y rendimiento de forraje de moringa oleífera. moringa. Loreto - Rodriguez Sanjurjo, Erika Maria (2024)
The production of quality plant feed is one of the priorities of the Faculty of Agronomy for livestock nutrition in the tropical area of Loreto and this paper is entitled "POULTRY MEAT DOSAGE ON THE VEGETATIVE CHARACTERISTICS AND FORAGE YIELD OF Moringa oleífera. MORINGA. LORETO". With a randomized complete block design, with treatments T0 (control), T1 (10 tons of chicken manure/ha), T2 (20 tons of chicken manure/ha and T3 (30 tons of chicken manure/ha) the following conclusions were reached: it was proven that Moringa oleífera. MORINGA reacts positively to increasing doses of chicken manure. That for the dependent variables of this research work, treatment T3 (30 tons of chicken manure/ha) showed the best values in plant height with 1.45 meters, green matter with 1.52 kilos/m2, dry matter of 0.29 kilos/m2, percentage of coverage of 81 percent, with respect to yield, treatment T3 (30 tons of chicken manure/ha) obtained 15,200 kilos per hectare under the agroclimatic conditions of the area.